A case of unhealing skin ulcer with iatrogenic Cushing’s syndrome (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Cutaneous Leishmaniasis is a rare disease in South-East Asian countries like Bangladesh, often presenting as skin lesions, ulcers or granulomatous plaques on the arm or back. As the disease is uncommon, high index of suspicion is required for the diagnosis. We are presenting a case of cutaneous Leishmaniasis in a migrant Bangladeshi worker in the Kingdom of Saudi Arabia (KSA). The case was initially treated with antibiotics, emollients and systemic steroid for a long time. However, the disease progressed, and the patient developed features of iatrogenic Cushing syndrome. The diagnosis was confirmed with a skin biopsy, which revealed Leishmania parasite. He received treatment with Injectable liposomal Amphotericin B (LAmB) and oral Miltefosine with promising clinical response. Clinicians should be vigilant while treating non-healing ulcers, and consider CL when there is history of travelling to CL endemic areasJ Bangladesh Coll Phys Surg 2023; 41(4): 334-337